2011
DOI: 10.1111/j.1467-9922.2010.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Explicit and Implicit Instruction on Free Written Response Task Performance

Abstract: A classroom study was designed to test the hypothesis that explicit knowledge is used by second-language (L2) learners in a free written response task if that knowledge is present. Eighty-one 12-18-year-old learners of Dutch as an L2 took part in a computerassisted language learning experiment receiving either explicit or implicit instruction about two grammar structures. The ability to use these structures was measured at three points in time by means of an untimed grammaticality judgment task and a free writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 45 publications
5
47
3
Order By: Relevance
“…However, empirical data of Andringa et al (2011) did suggest that explicit knowledge can benefit implicit learning and knowledge. A free written response task and a written grammatical judgment task (GJT) were used as measures of implicit and explicit knowledge to assess the effectiveness of implicit and explicit instruction for speakers of different first language (L1) backgrounds in their acquisition of two structures of Dutch.…”
Section: How Explicit Knowledge Affects Online L2 Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…However, empirical data of Andringa et al (2011) did suggest that explicit knowledge can benefit implicit learning and knowledge. A free written response task and a written grammatical judgment task (GJT) were used as measures of implicit and explicit knowledge to assess the effectiveness of implicit and explicit instruction for speakers of different first language (L1) backgrounds in their acquisition of two structures of Dutch.…”
Section: How Explicit Knowledge Affects Online L2 Processingmentioning
confidence: 99%
“…If only the studies that potentially meet the mentioned criteria are considered (see Andringa et al, 2011, for a review), it can be concluded that there is still little solid evidence that explicit knowledge helps learners in becoming proficient users of the L2. Andringa et al (2011) reviewed studies that compared explicit and implicit instruction conditions and used spoken or written free production tasks as measures of implicit knowledge (e.g., Day & Shapson, 2001;Mackey & Philp, 1998;Muranoi, 2000;Sanz & Morgan-Short, 2004;VanPatten & Sanz, 1995; HOW EXPLICIT KNOWLEDGE AFFECTS ONLINE L2 PROCESSING 5 Williams & Evans, 1998).…”
Section: How Explicit Knowledge Affects Online L2 Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the debate in this line of research centers on the validity of the measures used to ascertain absence of awareness (Hama & Leow, 2010 ;Leow, 2000 ;Rebuschat, 2013 ;Williams, 2005 ). Similarly, many have stressed the urgent need for tests that can measure implicit and explicit knowledge separately to settle questions about a potentially facilitative role that explicit knowledge can play in the acquisition of implicit knowledge (Andringa, de Glopper, & Hacquebord, 2011 ;R. Ellis, 2004R.…”
Section: Measurement Issuesmentioning
confidence: 99%